The unpublished Allegation of Gregorio Mayas in defense of the patronage of the seven churches of Teruel (History Journal «Jerónimo Zurita», 2022)
The present work involves the study of the unpublished Allegation in defense of the patronage of the seven churches of Teruel that, secretly, was written in november 1745 by the Valencian scholar Gregorio Mayans, commissioned by the prosecutor of the Chamber of Castile Blas Jover. The analysis of the text allows to verify the change in strategy carried out by the Chamber in defense of the royal patronage, which would take shape with the binomial Jover-Mayans. On the other hand, it reflects the intelectual capacity of Mr. Gregorio to argue for royalties, based on the study of history, national laws, the right of conquest and tradition.
Keywords: Royal patronaje; Churchs of Teruel; Gregorio Mayans; Blas Jovere; Prosecutor of Chamber